Towards Sharia E-Commerce Regulation: Analysis of Gharar and Consumer Protection in Indonesia - Ahdiyatul Hidayah; Nurmu’izzatin Zaharatul Parhi (Saqifah: Jurnal Hukum Ekonomi Syariah, 2025)
The development of digital technology has changed the pattern of conventional transactions to be online-based through e-commerce. Although it offers convenience and efficiency, e-commerce transactions also have potential legal problems, especially related to the unclear product information, payment methods, and delivery systems, which lead to gharar elements. In sharia economic law, gharar is seen as a prohibited uncertainty because it has the potential to harm one party and injure the principle of justice in the contract. This research aims to examine the concept of gharar in the context of digital transactions and examine consumer protection mechanisms according to the perspective of sharia economic law. The method used is normative legal research with a qualitative approach through literature studies on classical and contemporary fiqh books, national regulations, and relevant fatwas. The results of the study show that e-commerce is prone to contain elements of gharar, both explicitly and implicitly. Therefore, consumer protection is needed that is not only based on positive law, but also integrates sharia principles such as honesty (sidq), clarity of contract (ablution al-'aqd), and trust. This study recommends the need for special regulations on sharia e-commerce and increasing digital muamalah literacy for the Muslim community.